Evolution of TWIN SISTER of FT (TSF) Genes in Brassicaceae - Yunyan Hu; Bo Liu; Chao Sun; Jing Liu; Xiaobo Wang; Feng Cheng; Jianli Liang; Xiaowu Wang; Jian Wu (Horticultural Plant Journal, 2016)
FT and its homolog, TWIN SISTER OF FT (TSF), act redundantly as integrators in floral transition pathways in Arabidopsis thaliana. The evolution of these key flowering regulatory genes during Brassicaceae speciation has not been well studied; therefore, we investigated their evolution in 13 sequenced Brassicaceae species. While the phylogenetic analysis indicated that FT gene evolution has followed two independent lineage-specific routes, TSF evolution does not appear to have been completely consistent within the Brassicaceae lineage I and lineage II division. The two TSF copies in the Thellungiella genus were divided into A and B groups in the phylogenetic analysis. Examination of conserved non-coding sequences and conserved domains within a 5 kb region upstream of the TSF start codon revealed the same group division inferred by the phylogenetic analysis. In addition, TSF genes retained syntenic relationships among genes in the same group, but not between group A and group B. The two copies of the TSF gene in the Thellungiella species were syntenic to the TSF genes in group A and group B, respectively. We also identified TSF-A gene residues in the syntenic region of group B species, but no TSF-B residues could be found in the group A syntenic region. Therefore, we inferred that the TSF genes in lineage II species experienced a duplication event after diversification from lineage I. Following their split from Thellungiella, Brassica species lost the ancestral TSF gene and retained the duplicated copy.